Genetic Animal Models for Arrhythmogenic Cardiomyopathy - Gerull, Brenda; Brodehl, Andreas (Frontiers in Physiology, 2020)
Arrhythmogenic cardiomyopathy is clinically defined since the 1980s and causes right or biventricular cardiomyopathy associated with ventricular arrhythmia. Although it is a rare cardiac disease, it is responsible for a significant proportion of sudden cardiac deaths especially in athletes. The majority of patients with arrhythmogenic cardiomyopathy carry one or more genetic variants in desmosomal genes. In the 1990s, several knock-out mouse models of genes encoding for desmosomal proteins involved in cell-cell adhesion revealed for the first-time embryonic lethality due to cardiac defects. Influenced by these initial discoveries in mice, arrhythmogenic cardiomyopathy received an increasing interest in human cardiovascular genetics leading to the discovery of mutations initially in desmosomal genes and later on in over 25 different genes. Of note, even in clinical routine genetic diagnostics are important for risk prediction of patients and their relatives with arrhythmogenic cardiomyopathy. Based on improvements in genetic animal engineering, different transgenic, knock-in or cardiac specific knock-out animal models for desmosomal and non-desmosomal proteins have been generated leading to important discoveries in this field. Here, we present an overview about the existing animal models of arrhythmogenic cardiomyopathy with a focus on the underlying pathomechanism and its importance for understanding of this disease. Prospectively, novel mechanistic insights gained from the whole animal, organ, tissue, cellular and molecular level will lead to the development of efficient personalized therapies for treatment of arrhythmogenic cardiomyopathy.